1984
DOI: 10.3109/15563658408992586
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chlorpromazine, Haloperidol and Pimozide in the Treatment of Phencyclidine Psychosis: Da-2 Receptor Specificity

Abstract: Three neuroleptics were used to treat phencyclidine (PCP) psychosis. These included chlorpromazine, a DA-1 and DA-2 dopamine antagonist with noradrenergic effects; haloperidol, a predominantly DA-2 antagonist with noradrenergic effects; and pimozide a predominantly DA-2 antagonist with no noradrenergic activity. Three cohorts of randomly selected young white adult males were studied. Responses to haloperidol and pimozide were statistically equivalent and both were significantly superior to chlorpromazine. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Nevertheless, the present in vitro data are at least consistent with the clinical data on this topic. That is, the clinical agonist actions of phencyclidine and LSD in eliciting psychotic symptoms are selectively treated in the hospital emergency room by haloperidol and other dopamine D2-selective antagonists, 28,29 supporting the idea that dopamine D2 receptors are the primary target for eliciting psychotic symptoms. Although it has been claimed that psychotic symptoms elicited by ketamine are not blocked by haloperidol, 3 Giannini et al 30 have found that 5 mg of intramuscular haloperidol caused significant reductions in psychotic symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, the present in vitro data are at least consistent with the clinical data on this topic. That is, the clinical agonist actions of phencyclidine and LSD in eliciting psychotic symptoms are selectively treated in the hospital emergency room by haloperidol and other dopamine D2-selective antagonists, 28,29 supporting the idea that dopamine D2 receptors are the primary target for eliciting psychotic symptoms. Although it has been claimed that psychotic symptoms elicited by ketamine are not blocked by haloperidol, 3 Giannini et al 30 have found that 5 mg of intramuscular haloperidol caused significant reductions in psychotic symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…39,40 More importantly, studies in patients with PCP-induced psychosis (the state that the animal models are presumably reflecting) show that typical antipsychotics such as haloperidol and pimozide (a selective D 2 / 3 blocker) are much more effective than placebo, and result in remission of all symptoms. [41][42][43] To our knowledge there are no data on the use of atypical antipsychotics in clinical PCPinduced psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known clinically that haloperidol (which has a high affinity for D2 but a low affinity for glutamate receptors) effectively alleviates the psychosis secondary to phencyclidine or ketamine. 32,33 Moreover, it appears that glutamate receptor agonists such as pomaglumetad methionil and LY404,039 do not have any antipsychotic efficacy. A four-week trial had little or no efficacy against positive symptoms or negative signs when compared with olanzapine.…”
Section: Clozapine and Glutamate Receptorsmentioning
confidence: 99%